Selectively enhanced magnetic vertical conductive coupling among magnetic localized surface plasmons - Wang, Zhuoyuan (2021)
We present the experimental observation of selectively-enhanced magnetic vertical conductive coupling among magnetic localized surface plasmons. The system consists of two vertical conductively connected metallic spiral structures (MSSs) whose magnetic dipole modes interact with the help of strong conduction current through the connecting rod, exhibiting a much stronger magnetic coupling than that in an unconnected MSSs dimer. In particular, one of the two split coupled magnetic dipole modes will shift dramatically to a much lower frequency, while the other split magnetic dipole mode remains almost unaffected compared to the unconnected MSSs dimer. We also demonstrate that the vertical couplings among the electric dipole mode are kept almost unchanged even when the two MSSs are connected.